A study of the response of the root meristem of maize to acute doses of ionizing radiations - Fenner, Dennis Gordon (Department of Biological Sciences, 2020)
At the commencement of any studies in radiobiology it is necessary to decide on a suitable system for investigation, either animal or plant.